COMPARISON BETWEEN LUMP SUM AND UNIT PRICE CONTRACTS IN CONSTRUCTION OF RESIDENTIAL PROJECTS IN KURDISTAN REGION OF IRAQ - CASE STUDY - MOHAMMED, GAYLAN M.; OTHMAN, SHAMAL ALI (Journal of Duhok University, 2023)
Contract management is generally thought to be a significant supporter of project success, and it would increase the probability of success. In residential projects, project cost management is essential. As there are different cost-control approaches depending on the type of contract. The major distinction between Lump-sum and Unit-Price basis contracts is critical. This study focused on showing the strengths and weaknesses of two main contract types which are Lump sum (fixed price) and unit price contracts from the Expert's point of view, people concerned in the field of project management and construction industry. Case studies include residential projects that were successfully implemented in the last five years in the Iraq-Kurdistan region. The study was done by comparing both types of contracts in various fields. (Cost management, time management, facing challenges). The strengths and weaknesses of each contract type were determined based on the view of 30 expert people who responded to a questionnaire survey. The results clearly show that the Lump sum contract type has strong points in clear project cost and clear profits (60% of experts agreed) amount. Also, it is simpler in management (63.3% of experts agreed) and can achieve a higher completion rate in a shorter period compared to projects executed by unit price contract (56.7% of experts agreed) While having inflexibility with design changes and errors (66.7% of experts agreed) and a less transparent and impartial bidding process (60% of experts agreed) can be viewed as a weak point of the lump sum contract. However, the Unit Price contract type has strong points in flexibility with design changes and errors (66.7% of experts agreed), while has less clear project cost and less clear profits amount (60% of experts agreed). Since Contract type is the critical element for the project owners and beneficiaries